Responding to student mental health concerns in social work education: reflective questions for social work educators. Issue 6 (18th August 2019) - Todd, Sarah; Asakura, Kenta; Morris, Brenda; Eagle, Brooke; Park, Gareth
ABSTRACT: In this paper, we explore ways in which social work educators might respond to students who report that mental health issues underlie their difficulty in meeting core competencies, or otherwise use the language of mental health to describe their struggles to succeed in social work programs. We discuss various trends in policy responses in Canada, the US, the UK, and Ireland. While there are general policy trends, it is clear that responding to these kinds of issues requires the development of highly flexible and situated policy processes that can respond to student realities, concern for students' rights and privacy, and an awareness of potential discrimination against students. These processes also need to meet the specificities of practicums, particular institutional policies, the mandates of relevant professional bodies, and the precise local legislative framework that shapes these situations. Given these varying contexts, in this conceptual paper, we used a framework on disability that is informed by critical theory to engage existing school policies and propose a set of reflective questions that can guide schools of social work to create an overall responsive environment. These reflective questions are designed to help social work educators balance the rights and needs of students with the professional and institutional demands that students meet core competencies in their education.